Results of implementation of the pilot project of management system for learning and concomitance of the educational, methodological and scientific activities “JETIQ” - Bisikalo, Oleg; Palamarchuk, Yevhen; Kovalenko, Olena (Видавництво Наукового товариства ім. Шевченка, 2017)
Автори представляють результати впровадження системи управління навчанням. Комплексна система складається з окремих модулів, які дозволяють сформувати персональний репозиторій електронних ресурсів. Таке інформаційне сховище є програмною платформою для здійснення моніторингу результатів навчання, наукової та методичної діяльності викладачів. Система охоплює всі основні процеси освітньої діяльності та побудована за принципами екосистеми. Кожен блок системи є взаємопов’язаним з іншими, a інформація у системі динамічно оновлюється. Основними базами даних є дані викладачів, співробітників та студентів, результати оцінювання студентів шляхом поточного контролю (електронний журнал) та підсумкового контролю (електронні відомості, електронна залікова книжка, зведені звітні таблиці). Методичне забезпечення кожної дисципліни формується як структурована база знань в навігаторі дисципліни, який містить такі модулі електронних ресурсів як файли конспекту лекцій, методичних вказівок, наукових статей, посібники та підручників; відео та аудіо-підкасти; тестові завдання; зовнішні і внутрішні посилання тощо. Динамічні WEB-сайти кафедр та підрозділів формують зручне середовище автоматичної звітності, інтеграції з іншими електронними ресурсами.

In this article is presented successful results of implementation of the management training system JetIQ. This integrated system consists of separate modules, which allow to form a personal environment (space) of electronic resources. Such information environment is formed by a programmatic platform and is used for monitoring of the learning results, scientific and methodological activities of teachers. This system covers all major processes of educational activity. It is built on ecosystem structure principles. Each block of the system is interconnected with other ones and the information in it is dynamically updated. The main databases include teachers data, data of employees and students. The results of students evaluation are based on the current control (the electronic teacher’s journal) and on the final control (by electronic gradebook, summary reports etc). The methodological support of each discipline is formed as a structured knowledge which is based on the electronic instrument - discipline navigator. It contains the following modules of electronic resources: lectures summary, guidelines, scientific articles, manuals and textbooks; video and audio resources; test tasks; different links and so on. Dynamic websites of university departments form the comfortable environment for automatic reporting, integration with other electronic resources.
Keywords: інформаційні системи управління навчанням; JetIQ; репозиторій; WEB-сайт кафедри; електронний журнал; навігатор дисципліни; електронний ресурс; інформаційна екосистема; information management systems; JetIQ; repository; environment; department WEB-site; electronic journal; discipline navigator; electronic resource; information ecosystem; 004; 378.147(045)